A gendered lens on COVID-19 employment and social policies in Europe. (19th February 2021) - Cook, Rose; Grimshaw, Damian
ABSTRACT: The COVID-19 outbreak and resultant economic crisis has led to governments in Europe taking extraordinary action to support citizens. Bodies such as the International Labour Organisation (ILO) recommend such measures should include targeted support for the most affected population groups. Women form one of these groups, with disproportionate impacts on their employment and economic resources already documented. Although the disruption brought about by the COVID-19 crisis has the potential to reshape gender relations for everyone's benefit, there are concerns that the crisis will exacerbate underlying gender inequalities. Though these impacts are likely to be felt globally, public policy has the potential to mitigate them and to ensure a gender-sensitive recovery from the crisis. This paper introduces a gendered lens on the employment and social policies European countries have established since the crisis, with a brief comparative analysis of short-time working schemes in four countries – Germany, Italy, Norway, and the UK. Ongoing research seeks to extend the comparative, gendered analysis of the design, access and impacts of COVID-19 employment and social policies across Europe.